Metabolic energy decline coupled dysregulation of catecholamine metabolism in physiologically highly active neurons: implications for selective neuronal death in Parkinson’s disease - Wimalasena, Kandatege; Adetuyi, Oluwatosin; Eldani, Maya (Frontiers in Aging Neuroscience, 2024)
Parkinson’s disease (PD) is an age-related irreversible neurodegenerative disease which is characterized as a progressively worsening involuntary movement disorder caused by the loss of dopaminergic (DA) neurons in substantia nigra pars compacta (SNpc). Two main pathophysiological features of PD are the accumulation of inclusion bodies in the affected neurons and the predominant loss of neuromelanin-containing DA neurons in substantia nigra pars compacta (SNpc) and noradrenergic (NE) neurons in locus coeruleus (LC). The inclusion bodies contain misfolded and aggregated α-synuclein (α-Syn) fibrils known as Lewy bodies. The etiology and pathogenic mechanisms of PD are complex, multi-dimensional and associated with a combination of environmental, genetic, and other age-related factors. Although individual factors associated with the pathogenic mechanisms of PD have been widely investigated, an integration of the findings to a unified causative mechanism has not been envisioned. Here we propose an integrated mechanism for the degeneration of DA neurons in SNpc and NE neurons in LC in PD, based on their unique high metabolic activity coupled elevated energy demand, using currently available experimental data. The proposed hypothetical mechanism is primarily based on the unique high metabolic activity coupled elevated energy demand of these neurons. We reason that the high vulnerability of a selective group of DA neurons in SNpc and NE neurons in LC in PD could be due to the cellular energy modulations. Such cellular energy modulations could induce dysregulation of DA and NE metabolism and perturbation of the redox active metal homeostasis (especially copper and iron) in these neurons.